Fundamental British Values, Michel Foucault, and Religious Education Teacher Subjectivity A Critical Investigation - Farrell, Francis (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"This book presents a rich and important account of teachers as talking back to the contradictory and insidious nature of enforcing Prevent and FBVs in education, and as problematising power. I am heartened by teachers themselves critically and creatively encouraging inclusive and anti-racist approaches to exploring multiculturalism, identities and belongings to Britain through religious education teaching in the classroom. Farrell's book is a must-read for all teachers, and especially for trainee teachers who are grappling with the influence of exclusionary and assimilatory discourses around educational policy in schools." - Sadia Habib, Lecturer in Education, University of Manchester, UK. This book contributes to the small but growing critical literature on fundamental British values and the Prevent strategy in the British education system. Focusing specifically on RE, a subject concerned with multiculturalism, difference and pluralism, the book will argue that there is a tension between the aims of RE and the agenda of fundamental British values. The author argues that fundamental British values and the requirements of the Prevent duty (2015) amount to a securitization of education which fundamentally alters the relationship between teachers and learners. The book presents these developments in education policy as a radical discursive shift: drawing from in depth individual and group interviews with 52 secondary teachers of religious education, the book foregrounds the views of BAME teachers and argues for a nuanced and inclusive approach to civic and values education. Francis Farrell is Senior Lecturer in Theology and Religion at Edge Hill University, UK.
Chapter 1: Introduction -- Chapter 2: Britishness in Post War Politics and Policy: Precursors to British values -- Chapter 3: Crisis Racism and the introduction of Fundamental British values -- Chapter 4: Multiculturalism, Religious Education and Fundamental British Values -- Chapter 5: Research on British Values -- Chapter 6: Foucault and Fundamental British Values -- Chapter 7: Teacher Narratives, Parrēsia and the Courage of Truth -- Chapter 8: Dividing practices: RE teachers' views of fundamental British Values -- Chapter 9: Brexit, Religious Education and Fundamental British Values -- Chapter 10: Concluding Thoughts: Working the Cracks.
Keywords: Educational sociology; Schools; Education and state; Teachers -- Training of; Religion; Sociology of Education; School and Schooling; Educational Policy and Politics; Teaching and Teacher Education; Religion